Study on the effect of different rootstocks on cane biochemical composition in grape varieties - N A DESHMUKH; S D GAT; S R TAKALE; S R SINHASANE; P H NIKUMBHE; R G SOMKUWAR (The Indian Journal of Agricultural Sciences)
The present investigation aimed to study the effect of different rootstocks, viz. Dogridge (V. champini), 110R (V. berlandieri × V. rupestris), 140RU (V. berlandieri × V. rupestris), and 1103P (V. berlandieri × V. rupestris) on cane biochemical composition, yield and berry quality of new grape varieties. viz. Manjari Medika, Manjari Naveen, Manjari Kishmish along with Thompson Seedless. Experiment was conducted at ICAR-National Research Centre for Grapes, Pune, Maharashtra, during the year 2022–23 and 2023–24. Results showed that cane biochemical content varied significantly among the different rootstock-variety combinations influencing the grapevine fruitfulness, yield and berry quality. Among the rootstock variety combinations, grape variety Manjari Medika grafted on 140RU rootstock exhibited highest levels of carbohydrate (108.05 mg/g), proline (5.07 µmoles/g), and protein (5.90 mg/g) content. However, Manjari Naveen grafted on 110R showed the highest tannin (5.71 mg/g) and phenol (4.43 mg/g) content. Similarly, Manjari Medika × 140RU rootstock exhibit highest fruitfulness (95.74%), yield/vine (18.47 kg) with optimum berry quality, while lowest fruitfulness was recorded in Thompson Seedless × 1103P (81.13%) and minimum yield/vine in Manjari Naveen × Dogridge (8.46 kg), respectively. The study identified a notable linear correlation between yield per vine and cane biochemical, viz. carbohydrates, phenol, tannin, proline and protein. Further, Manjari Medika × 140RU is suggested as promising rootstock-variety combinations for quality grape production at tropical climate of India.